Microfluidic nutrient gradient–based three-dimensional chondrocyte culture-on-a-chip as an in vitro equine arthritis model. (September 2019) - Rosser, J.; Bachmann, B.; Jordan, C.; Ribitsch, I.; Haltmayer, E.; Gueltekin, S.; Junttila, S.; Galik, B.; Gyenesei, A.; Haddadi, B.; Harasek, M.; Egerbacher, M.; et al.
Abstract: In this work, we describe a microfluidic three-dimensional (3D) chondrocyte culture mimicking in vivo articular chondrocyte morphology, cell distribution, metabolism, and gene expression. This has been accomplished by establishing a physiologic nutrient diffusion gradient across the simulated matrix, while geometric design constraints of the microchambers drive native-like cellular behavior. Primary equine chondrocytes remained viable for the extended culture time of 3 weeks and maintained the low metabolic activity and high Sox9, aggrecan, and Col2 expression typical of articular chondrocytes. Our microfluidic 3D chondrocyte microtissues were further exposed to inflammatory cytokines to establish an animal-free, in vitro osteoarthritis model. Results of our study indicate that our microtissue model emulates the basic characteristics of native cartilage and responds to biochemical injury, thus providing a new foundation for exploration of osteoarthritis pathophysiology in both human and veterinary patients.